2007
DOI: 10.1002/dvdy.21199
|View full text |Cite
|
Sign up to set email alerts
|

From segment to somite: Segmentation to epithelialization analyzed within quantitative frameworks

Abstract: One of the most visually striking patterns in the early developing embryo is somite segmentation. Somites form as repeated, periodic structures in pairs along nearly the entire caudal vertebrate axis. The morphological process involves short-and long-range signals that drive cell rearrangements and cell shaping to create discrete, epithelialized segments. Key to developing novel strategies to prevent somite birth defects that involve axial bone and skeletal muscle development is understanding how the molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 89 publications
1
23
0
1
Order By: Relevance
“…FGF8 and RA couple antagonistically within cells to select either high-RA or high-FGF8 states in a bistable manner (Diez del Corral et al, 2003;Goldbeter et al, 2007). Above a threshold level of FGF8, individual cells in the PSM exhibit spontaneous oscillations in expression levels of many genes, especially those belonging to the Notch, Wnt and FGF cascades (Palmeirim et al, 1997;Dequeant et al, 2006;Kulesa et al, 2007), with a period which depends on cytoplasmic FGF8 levels. Neighboring cells' oscillators synchronize via Delta-Notch signaling (Horikawa et al, 2006).…”
Section: From Genetic Oscillators To Adhesion/repulsion-protein mentioning
confidence: 99%
See 1 more Smart Citation
“…FGF8 and RA couple antagonistically within cells to select either high-RA or high-FGF8 states in a bistable manner (Diez del Corral et al, 2003;Goldbeter et al, 2007). Above a threshold level of FGF8, individual cells in the PSM exhibit spontaneous oscillations in expression levels of many genes, especially those belonging to the Notch, Wnt and FGF cascades (Palmeirim et al, 1997;Dequeant et al, 2006;Kulesa et al, 2007), with a period which depends on cytoplasmic FGF8 levels. Neighboring cells' oscillators synchronize via Delta-Notch signaling (Horikawa et al, 2006).…”
Section: From Genetic Oscillators To Adhesion/repulsion-protein mentioning
confidence: 99%
“…Experimentally, animal species differ in the cell rearrangements which create the somite-PSM border and how aggressively new somites pull apart from the PSM (Kulesa et al, 2007). In Xenopus embryos, two short, discrete fissures start from both the medial and lateral edges of the PSM and expand gradually towards the middle of the PSM to form a stable somite-PSM border (Afonin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For example, vertebrate segmentation is controlled by the interplay between Notch and FGF, including multiple negative feedbacks. Interdisciplinary approaches have revealed that oscillatory gene networks constitute the segmentation clock machinery (11,12).…”
mentioning
confidence: 99%
“…Differential gene expression patterns arising from such a mechanism direct the morphological changes that give rise to somites (Kulesa et al, 2007). Firm evidence for both the clock and wavefront has been gathered over the past 10 yrs, so that both are now characterized to good extent by the molecular players that seem to play key roles in their existence.…”
Section: Oscillators During Vertebrate Segmentationmentioning
confidence: 99%